Metatarsophalangeal Arthrodesis through the Modified Steel Basket Technique in Foal - Shade, Jackson; Augusto Amaro, Flávia do Prado; Poncio da Silva, João Batista; Pauls Sotelo, Eric Danilo; Barcellos, Luiza Costa; Guedes, Rogerio Luizari; da Silva Machado, Luiz Fagner; Dornbusch, Peterson Triches (Acta Scientiae Veterinariae, 2019)
Background: The metacarpophalangeal and metatarsophalangeal joints are very demanded during high intensity exercises, and may be affected by osteoarthritis, fractures, luxations and rupture of the suspensory apparatus. Thus, arthrodesis may be indicated to restore joint stability and accelerate the ankylosis process. The most commonly used surgical techniques have been associated with postoperative complications, including infection and failure of the implants, so it is important to develop procedures that are less invasive procedures and promoting stable fixation. Therefore, the aim of this work is to report the use of the modified steel basket technique for metatarsophalangeal arthrodesis in a foal with hyperextension of the joint due to rupture of the digital flexor muscles. Case: A 2-day-old male foal was admitted to clinical care, presenting multiple cutaneous wounds caused by dogs bites, located in the tarsus and thigh of the hindlimb. The animal presented in standing position and had no difficulty of movement, being initially treated through daily cleaning of the cutaneous wounds and systemic antibiotic therapy. Hyperextension of the metatarsophalangeal joint was evidenced after 20 days, being approached through tenotomy and tendon shortening, followed by tenorrhaphy and immobilization for 30 days. Due to the failure of the treatment, it was opted for metatarsophalangeal arthrodesis by modified steel basket technique. The procedure involved the implantation of a steel basket of 25.0 mm in diameter x 25.0 mm long in a 24.0 mm hole created on the dorsal surface between the third metacarpal and the proximal phalanx. The basket was filled with bone extracted from drilling and fixed with two cortical screws at an angle of 25° toward proximoplantar and distoplantar direction. Immobilization of the limb was performed postoperatively with synthetic plaster cast for 45 days and, due to the persistence of lameness, maintained with Robert Jones banding and plantar splint for another 15 days. At 90 days after surgery, radiographic control showed signs of degeneration and joint fusion, and grade 2 claudication (1-5) was observed during locomotion. At six months after surgery, discrete claudication (grade 1/1-5) was evident. The aesthetic and functional result was considered satisfactory and the animal was then ridden and used for leisure. Discussion: In this report, arthrodesis was indicated due to hyperextension of the metatarsophalangeal joint caused by the rupture of the digital flexor muscles, since these structures, together with the suspensory apparatus, assist in the support of the joint. Several techniques have been descrited for arthrodesis of metacarpal/metatarsophalangeal joints in horses, being the technique described by Bramlage the most employed and successful one. However, complications related to the techniques such as infection and implant failure were evidenced in one study. The technique of the modified steel basket is characterized by the promotional of effective intervertebral arthrodesis in cases of cervical instability in horses. In this report, the technique was effective in promoting metatarsophalangeal arthrodesis, as well as easy and quick to perform. Therefore, it is suggested that the technique may be used as an alternative for metacarpal/metatarsophalangeal arthrodesis in horses with osteoarthritis or hyperextension of the joint due to suspensory apparatus failure. However, studies are needed to evaluate the effectiveness of the technique in metacarpophalangeal arthrodesis in adult horses.